2014
DOI: 10.1371/journal.pone.0098207
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Induces Apoptosis and Cell Cycle Arrest Mediated by Oxidative Stress, AMPK and FOXO3a in MCF-7 Breast Cancer Cells

Abstract: Recent studies have demonstrated that the anti-diabetic drug, metformin, can exhibit direct antitumoral effects, or can indirectly decrease tumor proliferation by improving insulin sensitivity. Despite these recent advances, the underlying molecular mechanisms involved in decreasing tumor formation are not well understood. In this study, we examined the antiproliferative role and mechanism of action of metformin in MCF-7 cancer cells treated with 10 mM of metformin for 24, 48, and 72 hours. Using BrdU and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
177
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(216 citation statements)
references
References 75 publications
26
177
3
6
Order By: Relevance
“…6 Adjusted model contains all variables in " 1" along with BMI prior to diagnosis (in individuals with BMI available). 7 Adjusted model contains all variables in " 1" along with smoking prior to diagnosis (in individuals with smoking available). 8 Adjusted model contains all variables in " 1" along with tumour grade prior to diagnosis (in individuals with grade available).…”
Section: Cancer Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…6 Adjusted model contains all variables in " 1" along with BMI prior to diagnosis (in individuals with BMI available). 7 Adjusted model contains all variables in " 1" along with smoking prior to diagnosis (in individuals with smoking available). 8 Adjusted model contains all variables in " 1" along with tumour grade prior to diagnosis (in individuals with grade available).…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…[2][3][4] Although not fully elucidated, the potential anti-tumour effects of metformin are thought to be due to inhibition of the mammalian target of rapamycin (mTOR) signalling pathway, resulting in suppression of cellular proliferation 5 tumour cell migration and invasion 6 as well as an increase in apoptosis. 7 Despite mounting preclinical evidence supporting a possible therapeutic role for metformin in colorectal cancer, only two epidemiological studies have evaluated the impact of post-diagnostic metformin exposure on cancer outcomes in colorectal cancer patients with type 2 diabetes. A Korean study of 595 colorectal cancer patients with type 2 diabetes reported substantial reductions in risk of colorectal cancerspecific and all-cause mortality among metformin users after diagnosis.…”
mentioning
confidence: 99%
“…Several laboratory studies show that metformin use is associated with cell growth suppression in breast cancer cells, possibly mediated by activation of 5'-adenosine monophosphate-activated protein kinase (AMPK) [5,6]. Observational studies also show that metformin use is associated with a 20-30% lower breast cancer incidence [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Выбор для работы именно этого соединения был обусловлен 2 основными факторами. С одной стороны, метформин принадлежит к совершен-но отличному от стероидов классу соединений, и его противоопухолевая активность ассоциирована, преиму-щественно, с подавлением АМРК и mTOR-сигналинга [14]. С другой стороны, в основе приобретенной рези-стентности к метформину лежит компенсаторная реак-тивация сигнальных путей [7], как и в случае гормо-нальной резистентности, что могло свидетельствовать о существовании общих механизмов распространения обоих видов резистентности.…”
Section: заключениеunclassified